FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN BERBELANJADI HYPERMART DUTA MALL BANJARMASIN - HELMI, RAHMAN (At-Taradhi, 2015)
Abstract: The purpose of this study was to determine the effect of simultaneous cultural, social, personal, and the psychology of the consumers decision to shop at Hypermart Duta Mall Banjarmasin, and to determine the dominant influence between the cultural, social, personal, and the psychology of the consumers decision to shop at Hypermart Duta Mall Banjarmasin. The analytical method used is multiple linear regression with SPSS. The results of the multiple linear regression analysis showed there are significant cultural, social, personal and psychological simultaneously to the consumers decision to shop at Hypermart Duta Mall Banjarmasin, seen from the sig value obtained was 0,000. Partially there are three factors that influence the consumers decision to shop at Hypermart Duta Mall Banjarmasin, namely, social factors, personal, and psychology. The dominant psychological factors influence the decision of consumers to shop at Hypermart Duta Mall Banjarmasin.